4D-TExS: A new 4D lattice-QCD equation of state with extended density coverage - Jahan Johannes; Abuali Ahmed; Borsányi Szabolcs; Kahangirwe Micheal; Parotto Paolo; Pásztor Attila; Ratti Claudia; Shah Hitansh; Trabulsi Seth A. (EPJ Web of Conferences)
Although calculations of QCD thermodynamics from first-principle lattice simulations are limited to zero net-density due to the fermion sign problem, several methods have been developed to extend the equation of state (EoS) to finite values of the B, Q, S chemical potentials. Taylor expansion around µi = 0 (i = B, Q, S) enables to cover with confidence the region up to µi/T < 2.5. Recently, a new method has been developed to compute a 2D EoS in the (T, µB) plane. It was constructed through a T -expansion scheme (TExS), based on a resummation of the Taylor expansion, and is trusted up to densities around µB/T = 3.5. We present here the new 4D-TExS EoS, a generalization of the TExS to all 3 chemical potentials, expected to offer a larger coverage than the 4D Taylor expansion EoS. After explaining the basics of the T -Expansion Scheme and how it is generalized to multiple dimensions, we will present results for thermodynamic observables as functions of temperature and both finite baryon and strangeness chemical potentials.